Deficient of glycosylation site in the envelop protein attenuated Zika virus replication in mosquito cells - Wang, Wen-Jing; Wang, Zi-Han; Li, Jing; Ma, Sai-Ya; He, Mei; Liu, Meng-Xuan; Zhan, Yu-Fei; Jin, Feng; Qu, Guosheng; Yin, Chunhong; Tong, Jie (Frontiers in Microbiology, 2025)
IntroductionThe Zika virus (ZIKV) envelope (E) protein is critical for viral replication and host interactions. Although glycosylation of the E protein is known to influence viral infectivity and immune evasion, the specific functional roles of E protein glycosylation in ZIKV infectivity in mosquito cells remain unclear.MethodsIn this study, we generated a deglycosylation mutant ZIKV with a T156I substitution in the E protein and investigated its effects on viral replication and viral-host interactions in mosquito C6/36 cells.ResultsOur results demonstrated that the T156I mutant exhibited attenuated replication compared to the wild-type virus during the early stages (0-24 hours) post-virus infection in mosquito C6/36 cells. This attenuation was associated with reduced E protein expression, which was regulated at the post-transcriptional level. RNA sequencing further revealed that the T156I mutation significantly altered virus-host interactions, particularly affecting the extracellular matrix (ECM) signaling pathway. Notably, several genes involved in the ECM signaling pathway, including THBS1, ITGAL, IL-1A, and CXCL8, were found to inhibit the T156I mutant but not the wild-type ZIKV. Structural analysis and in silico molecular docking suggested that the T156I mutation impaired the stability of the E protein dimer rather than its interactions with neutralizing antibodies.DiscussionCollectively, these findings provide novel insights into the role of E protein glycosylation in ZIKV infection, and may have significant implications for anti-ZIKV strategies.